Syphilis ascendant: a brief history and modern trends. Issue 1 (December 2016) - Willeford, Wesley; Bachmann, Laura
Abstract To provide a miniature review of recent literature surrounding a brief history of syphilis, to discuss the recently increasing incidence of syphilis, to discuss recent United State Preventative Service Task Force recommendations for syphilis screening, and to discuss congenital syphilis. The literature review was conducting using PubMed with the following search terms: syphilis, congenital syphilis, MSM and syphilis, prenatal syphilis, neurosyphilis, and other related terms. Treponema pallidum has been a constant, and unwanted, companion of humankind since antiquity. This sexually transmitted infection (STI) has the potential to affect virtually every rung of society—young and old, rich and poor, but it has a proclivity for the most vulnerable groups among us. Since record high rates of infection in the World War II era, tremendous progress has been made in effectively controlling the infection, and this has been largely mediated by the efficacy of penicillin on the causative spirochete. However, 2014 data from the Centers for Disease Control and Prevention demonstrated a sharp increase in the rate of new cases of syphilis, predominantly in men who have sex with men. Additionally, the numbers of newly diagnosed cases of congenital syphilis are on the rise as well. In effect, a burgeoning crisis has come to the doorstep of the medical community. We are faced with changing attitudes regarding sexual interactions. The authors believe that geolocation dating and sex applications for smart phones increase the availability of sexual encounters. Pre-exposure prophylaxis may be leading to morelaissez-faire attitudes toward unprotected intercourse, and with increased opportunities for sexual encounters, co-infected states with other diseases may be altering the landscape of STIs. In 2016, in response to increasing rates of newly diagnosed syphilis, the United States Preventative Health Services Task Force reaffirmed the need for syphilis screening in at-risk populations. However, primary care physicians and advanced practice providers may not always be aware of which patients fall into that category. Due to the highly personal nature of discussing sexuality, sexual behavior may not be explored at all. Numerous challenges lie ahead of the infectious diseases, primary care, and public health communities in attempting to bend the curve of the ascendant rise in syphilis. To adequately combat this infection, sufficient funding will need to be provided to public health departments, adequate access to health care resources will be needed to allow for the necessary screening of patients, and primary care practitioners will need thoroughly engage with their patients to understand their sexual practices and to offer the necessary interventions.